Elastic Band Training Versus Multicomponent Training and Group-Based Dance on Morphological Variables and Physical Performance in Older Women: A Randomized Controlled Trial - Jordan Hernandez-Martinez; Eduardo Guzmán-Muñoz; Izham Cid-Calfucura; Francisca Villalobos-Fuentes; Daissy Diaz-Saldaña; Ignacia Alvarez-Martinez; María Castillo-Cerda; Tomás Herrera-Valenzuela; Braulio Henrique Magnani Branco; Pablo Valdés-Badilla (Life)
Background: This study aimed to analyze the effects of elastic band training (EBT) versus multicomponent training (MCT) and group-based dance (GBD) on waist circumference, body composition (body fat percentage and fat-free mass), and physical performance (handgrip strength, HGS; 30-s chair stand; timed up-and-go, TUG) in Chilean older women. Methods: This is a randomized controlled trial with three parallel groups: EBT (n = 10), MCT (n = 10), and GBD (n = 10). Two 60-min sessions per week for 8 weeks were dedicated to the interventions with pre- and post-assessments. A two-factor mixed ANOVA model with repeated measures was performed to measure the time × group effect. Results: Multiple comparisons revealed significant differences between EBT and MCT in the body fat percentage (p = 0.001; ES = 2.488, large effect) in favor of MCT, while HGS in the non-dominant hand (p = 0.044; ES = 0.158) was in favor of EBT. In the intragroup results, only the MCT significantly decreased the body fat percentage (p = 0.044; ES = 0.426, small effect), and EBT significantly increased HGS in the dominant (p < 0.001; ES = 0.977, large effect) and non-dominant (p < 0.001; ES = 0.583, moderate effect) hands and improved the 30-s chair stand (p = 0.003; ES = 1.612, large effect) test. The GBD did not report significant changes. Conclusions: MCT significantly reduced the body fat percentage regarding EBT, and EBT significantly improved HGS in the non-dominant hand regarding MCT, with no differences reported in the rest of the analyzed variables between the groups.